Determinants of Islamic Equity Funds Performance: Case Study of Indonesia - Fadel Rahman; Abdul Qoyum (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2022)
The performance of Islamic mutual funds is significant either for investors or policy-makers. Many factors affect the performance of Islamic mutual funds, such as internal factors, external factors (macroeconomics), and market index. This study aims to analyze the impact of the past return of Islamic mutual fund, BI rate, and the Jakarta Islamic Index (JII) on the performance of Islamic equity mutual funds. By employing panel data regression analysis, this study documented some interesting findings. The statistical testing revealed that BI rate, which is used as an indicator for external factors and JII (as Market factors), have a positive impact on the performance of Islamic equity mutual funds. In contrast, the past return does not affect the performance of Islamic equity funds. This study suggests that the investor must consider internal, and external factor in the investment activities.